Dermatitis artefacta. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2014)
The problem is not the diagnosis: the significant difference from any dermatological disease and exposed locations accessible to the dominant hand, the repetitiveness of the lesions make it easy (Fig. 1-4). Nor is important to identify the manner in which the subject self-inflicted the lesions. The real problem is to answer the call for help that comes from the patient. To do this we must first be able to "sympathizing" with the patient and his/her family. The psychologist is certainly the best qualified subject. However, the doctor who makes the diagnosis may be sufficient if he feels like it and has time to do it, especially if the psychiatric or psychological counseling are rejected by the family. In this case we found that the child self-inflicted the lesions in response to continued litigation of parents, abusive habits of the father and his dependence on alcohol. We heard the arguments of the father and we were able to convince him to take the path of weaning from his drug.